II. internationale Tagung der Keilschriftforscher sozialistischer Länder, Leipzig, 3.-6. April 1979 - Klengel, H.
35f.: Résumés (H. Limet, La formation du vocabulaire technique en sumérien; E. Lipiński, Sale, Transfer, and Delivery in Ancient Semitic Terminology).